La herramienta digital Lesson plan de simbaloo y su aporte en la creacion de itinerarios de aprendizaje digitales de los docentes de la Unidad Educativa Diez de Agosto de Vinces Provincia de Los Rios, periodo 2021-2022 - Romero Bustamante, Milene Lisbet (2022)
Education in the development of Information and Communication Technologies (ICT) has shown that adapting to pedagogical, technical and technological changes is essential to innovate the teaching-learning process at any of its academic levels or modality. The teacher faced a series of challenges caused by the pandemic due to covid-19, the use of new learning ecologies, the improvement and updating of his knowledge, the development of digital, cognitive, communicative and psychopedagogical skills allowed him to do critical and safe use of technologies in the training process of their students The objective of Symbaloo's Lesson plan digital tool is a platform that does not help organization and search, to obtain information through which they are not used, which through studies allows the use of it, and the use of methods that help the teacher improve the organization of search folders in the application. Education centers have seen the need to incline interactivity, making use of the digital collaborative environments that technology offers us. In the present study, useful concepts, data and results are updated on the use of the Symbaloo Lesson Plans tool, which allows teaching-learning especially in these times of online education, through the use of digital resources. It was obtained as results that teachers use ICT in their daily life, having full disposition to its application and discovery of spaces that help them to strengthen their learning. There is a moderate positive correlation between the variables where it is shown that the learning paths in Symbaloo constitute a positive methodological strategy to be used in the teaching-learning process.